Pengaruh Model Pembelajaran Berbasis Proyek terhadap Kemampuan Penalaran Adaptif Matematis Siswa Kelas VII SMPN 2 Lenek - Malsawati Triana; Masjudin Masjudin; Pujilestari (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2025)
Abstract: The aim of this study is to find out the influence of project-based learning models on the adaptive mathematical reasoning ability of students of grade VII at SMPN 2 Lenek. The method used in this research is experimental research. The design of this study is based on Pretest-Posttest Control Group Design. The samples used in this study were two classes where class VII A as experimental class and class VII B as control class, then both classes were given different treatment i.e. in experimental classes were treated with a project-based learning model whereas in control class were given conventional learning models, after given further treatment were given posttests to find out the final ability of students. The test results of the hypothesis obtained thitung = 4,741; ttabel = 1,045 or (thitung 4, 741 > ttabel 1, 045). Thus, it can be concluded that there is an influence of project-based learning models on the ability of mathematical reasoning students in SMPN 2 Lenek school year 2023/2024.